Falls among Older Adults: Screening, Identification, Rehabilitation, and Management - Silvia Giovannini; Fabrizio Brau; Vincenzo Galluzzo; Domenico Alessandro Santagada; Claudia Loreti; Lorenzo Biscotti; Alice Laudisio; Giuseppe Zuccalà; Roberto Bernabei (Applied Sciences, 2022)
A fall is an event where a person unintentionally and traumatically finds themselves on the floor or a lower level. Falls are very common, especially in the older adult population. One in four people falls at least once a year after age 65. Because of falls, there can be injuries, whereby there can be an impairment of health status. Fractures, reduced mobility, disability, and the need for institutionalization are potential consequences after falls. In older adult patients, especially frail ones, these types of complications are more common. There are several risk factors for falls. Falls generally result from a combination of factors operating simultaneously. Sarcopenia, cognitive impairment, or poly-pharmacotherapy are just a few examples of risk factors that are common in the older people. Through careful clinical evaluation, it is possible to identify risk factors and conditions predisposing to falls. In some cases, it is possible to correct these factors. Several types of treatment are available to restore the health status before the fall and prevent subsequent falls. Using multi-component interventions, the risk of falls can be effectively reduced. Aware that this review will not be exhaustive of such a broad topic, the purpose of this narrative review is to summarize relevant and recent evidence in the current literature to encapsulate fall-related risk factors, risk identification, fall prevention, and management, including various rehabilitation techniques. This article conforms to the Scale for Assessment of Narrative Review Articles (SANRA) guidelines.